The relevance of methane emissions from beef production and the challenges of the Argentinean beef production platform - Rearte, Daniel Horacio; Pordomingo, Anibal (Elsevier, 2018)
The livestock sector faces the challenge to respond to the growing demand for animal protein from an expanding population while reducing environmental impact through GHG emissions. Globally about 2.836 million tons of CO2-eq were emitted by the beef production sector equivalent to 46,2 kg CO2-eq per kg carcass weight (CW). From the 1.485 million cattle head spread out over the world, 82% are on extensive grazing systems while only 18% are on high productive intensive systems. Among the top ten beef exporter countries, five are located in Latin America accounting a quarter of the global stock and two of them, Argentina and Uruguay, produce on temperate pastures under grazing systems. In Argentina, the livestock area was reduced in favor of increasing the grain cropping area, which took place in the last two decades. Production systems were intensified to maintain cattle stock. Cattle programs changed from 100% pasture to pasture supplemented with cereal grains and conserved forages, and confinement on grain feeding for fattening was incorporated. Due to land sharing competition with cash crops, no increment of cattle stock is expected therefore improving production efficiency appears as the only way to increase beef production while reducing methane emissions intensity. Beef produced on intensive grazing systems on supplemented pastures maintained organoleptic, nutritional and lipid profile than that of beef produced on pure grazing systems.